Radiographic Progression in Patients With Ankylosing Spondylitis According to Uveitis Based on the Observation Study of Korean Spondyloarthropathy Registry - Hyunyi KOOK; So-hee JIN; Seunghun LEE; Seung-jin LEE; Tae-hwan KIM; Tae-Jong KIM (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate radiographic progression according to the presence or absence of uveitis in patients with ankylosing spondylitis (AS). Patients and methods: A total of 598 patients (529 males, 69 females, mean age 38.1±9.2 years; range, 18 to 73 years) from the Observation Study of Korean Spondyloarthropathy Registry who met the modified New York criteria for AS were included in this study. At baseline, all data were stratified into two groups according to the presence or absence of uveitis. Baseline and radiographic progression were assessed for five years in this registry. Modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) was read by two radiologists. Reliability was assessed using inter- and intra- class correlation coefficient for each radiograph. Comparison of mSASSS changes was analyzed by analysis of covariance model after adjusting for confounding factors. Results: The evaluation of mSASSS showed good agreement between the two readers. A total of 193 patients (32.27%) had a history of uveitis that presented at a mean age of 39.6 years, including 30 females (15.54%). There were statistically significant differences in age (p=0.01), sex (p=0.04), hip joint involvement (p<0.01), and human leukocyte antigen B27 carrier state (p=0.02) between the two groups according to uveitis. A simple comparison revealed no significant difference in mSASSS change for five years between the two groups (mean: 3.05±0.62 vs. 3.78±0.78, p=0.47). After adjusting for confounding factors in multiple comparisons by Bonferroni correction, patients with uveitis had no significant association with mSASSS change for five years (mean: 6.29±1.32 vs. 5.49±1.39, p=0.68). Conclusion: Our study confirms that there is no significant association between uveitis and radiographic progression in patients with AS after adjusting for confounding factors.